2007
DOI: 10.1186/1465-9921-8-90
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone is as effective as dexamethasone in a cockroach allergen-induced murine model of asthma

Abstract: Background: While glucocorticoids are currently the most effective therapy for asthma, associated side effects limit enthusiasm for their use. Peroxisome proliferator-activated receptor-γ (PPAR-γ) activators include the synthetic thiazolidinediones (TZDs) which exhibit anti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 66 publications
1
35
1
Order By: Relevance
“…37 Previous research has shown that DEX is an effective treatment for mouse models of inflammatory pulmonary disease. 36,38,39 Narala et al 38 compared pioglitazone to dexamethasone treatment in a CRA induced model of asthma and showed that these agents were equally effective at reducing airways resistance and lung mucus production. Therefore we expected that DEX would have a large effect on the inflammatory profile in our model of allergic pulmonary inflammation.…”
Section: Vaickus Et Almentioning
confidence: 99%
“…37 Previous research has shown that DEX is an effective treatment for mouse models of inflammatory pulmonary disease. 36,38,39 Narala et al 38 compared pioglitazone to dexamethasone treatment in a CRA induced model of asthma and showed that these agents were equally effective at reducing airways resistance and lung mucus production. Therefore we expected that DEX would have a large effect on the inflammatory profile in our model of allergic pulmonary inflammation.…”
Section: Vaickus Et Almentioning
confidence: 99%
“…Mouse models have shown that PPAR-c deletion from alveolar macrophages causes airway inflammation [8,9]. Furthermore, rosiglitazone inhibits the development of lipopolysaccharide (LPS)-induced airway neutrophilia [10], and pioglitazone inhibits allergic pulmonary inflammation in mice to a similar degree to corticosteroids [11]. In addition to its role in the inflammatory response, PPAR-c is also involved in the regulation of macrophage efferocytosis; PPAR-c deletion reduces macrophage clearance of apoptotic cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, these drugs inhibit the release of various cytokines from activated lymphocytes (12), monocytes (13), endothelial cells (14), microglia, and Phorbol 12-myristate 13-acetate-differentiated THP-1 cells (a human monocytic cell line) (15). In vivo, rosiglitazone and pioglitazone also effectively inhibit airway inflammation in various murine models of asthma (16,17). Most importantly, in a recent clinical trail, the inhalation of rosiglitazone improved lung function, and also reduced sputum IL-8 concentrations in steroid-resistant patients with asthma (18).…”
mentioning
confidence: 99%